CIPP-Based Evaluation of the Learning Process in Vocational High Schools: Student and Teacher Perspectives - Almes Gangga; Hasan Maksum; Ambiyar Ambiyar (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
This research evaluates the learning process in vocational high schools (SMK) using all four components of the CIPP (Context, Input, Process, Product) evaluation model from the perspectives of students and teachers. A descriptive-evaluative approach was employed involving 120 students and 25 teachers at SMK Negeri 1 Painan, selected through purposive sampling. Data were collected using validated questionnaires comprising 66 items for students and 59 items for teachers, structured around all four CIPP components, with particular depth on four Process sub-components: Teaching Strategy (P1), Media and Technology Use (P2), Student Interaction (P3), and Assessment Process (P4). The Context component received the highest scores from both groups (students: 76.4%; teachers: 83.2%), while the Product component scored the lowest among students (70.2%). The Process component was rated 72.5% by students and 80.2% by teachers overall, with Student Interaction (P3) as the strongest sub-component and Media and Technology Use (P2) as the most critical area for improvement. A consistent perception gap averaging 7.7 percentage points was identified across all components, with teachers rating program implementation more favorably than students throughout. These findings reveal systemic challenges in technology integration, assessment practices, and resource provision in vocational learning, and provide evidence-based recommendations for policy and instructional improvement in Indonesian vocational education.